THE INFLUENCE OF VILLAGE FUND MANAGEMENT ON THE WELFARE OF THE COMMUNITY OF BOTTO MALLANGGA VILLAGE, MAIWA DISTRICT ENREKANG DISTRICT - Nur Rezki Amalia; Wa Ode Rayyani; Alamsjah, Alamsjah (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to describe: Testing the Effect of Village Fund Management on the Welfare of the Community of Botto Mallangga Village, Maiwa District, Enrekang Regency. The type of research used in this research is quantitative research. The population in this study was the people of Botto Mallangga village, Maiwa sub-district, Enrekang district. The sampling technique uses the Slovin formula. The sample in this research was the Botto Mallangga village community. The number of samples processed in this research was 95 samples. In this research, the data sources used in data collection include primary data. The research instrument used in this study used a Likert scale. Based on the results of research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 22 application regarding the influence of service quality on village fund management on community welfare, it shows that village fund management has a positive and significant effect on community welfare. This is indicated by the calculated t value of 8.137 which is greater than the t table of 1.986 with a determination test value of 0.416 with a positive relationship